Diuron effects on photosynthesis and vertical migration of microphytobenthos: Potential rapid bioassessment of herbicide toxicity in coastal sediments. (September 2021) - Du, Guo-ying; Zhong, Xue-feng; Dupuy, Christine; Che, Shuai; Lavaud, Johann
Abstract: The effects of herbicide diuron on photosynthesis and vertical migration of intertidal microphytobenthos (MPB) assemblages were investigated using chlorophyll fluorometry. The results shown diuron ≤ 60 μg L −1 had no obvious effect on MPB vertical migration during 24 h indicated by consistent rhythm. Low concentration of 10 μg L −1 diuron had no significant influence on MPB photosynthesis throughout, however, high concentrations of 40, 50, and 60 μg L −1 had significant impacts exhibited by decreased parameters of maximum relative electron transport rate (rETRmax ), maximal PS II quantum yield (Fv /Fm ) and non-photochemical quenching (NPQ). For middle concentrations of 20 and 30 μg L −1, above decreased 3 parameters recovered sooner or later after 2 h or 16.5 h. Comparatively, rETRmax, Fv /Fm and NPQ are concentration dependent and more sensitive than other parameters in assessing diuron toxicity. This study revealed the potential of using MPB assemblages and chlorophyll fluorometry for rapid assessing diuron toxicity in coastal sediments. Highlights: The photophysiology of MPB in sediments is very sensitive to diuron. The vertical migration of MPB in sediments is not impacted by diuron. Adverse diuron effects increase together with increasing herbicide concentrations. Photosynthetic parameters Fv /Fm, rETRmax, and NPQ are the most sensitive to diuron. Well-plates combined with imaging fluorimetry provide a rapid toxicity monitoring.